Economic Crises in the Results of the Non-Financial Corporations Sector in the Czech Republic - Stanislava Hronová; Richard Hindls (Statistika: Statistics and Economy Journal, 2012)
In connection with the fi nancial and subsequent economic crisis, the role of non-fi nancial corporations is often discussed and the causes and eff ects of the crisis are analysed. Viewing two critical periods of economic development in the Czech Republic – the first in 1997–1998, and the second in 2009–2010 – we can see that non-financial corporations generated a high level of net borrowing in the fi rst instance and, on the contrary, a high level of net lending in the second instance. Regardless of the diff erent causes of the crises in the abovementioned periods, a natural question arises: what kind of transformation took place in the economic behaviourof non-fi nancial corporations between 1998 and 2008? Consequently, what was the source of their overall (and in a time of crisis, surprising) profi t in the crisis years of 2009 and 2010. When analysing the economic behaviour of the non-fi nancial corporations sector in the Czech Republic we will, naturally, base our considerations on the data from national accounts of the Czech Republic as published by the Czech Statistical Office and will also utilise the usual relative indices immediately implied by the national account ones, as well as indices whose construction is closer to the evaluation usual in corporate practice.